Report on the workshop on progress in wastewater treatment and Reuse Technology (PWTRT-2013) on 19th - 22nd December 2013 - Abu Zahrim Yaser; Chu Chi Ming; Rosalam Sarbatly (2014)
"The “Workshop on Progress in Wastewater Treatment and Reuse Technology (PWTRT-2013)” is organized with a key view to document the contribution and impact of research, development and innovations of the wastewater treatment industry especially on palm oil industry, oil and gas industry, dye, pulp and paper and urban wastewater. A total of 19 research scholars including 2 from China and 1 from Indonesia presented the latest work covering a wide variety of water treatment technologies in the lab scale as well industrial scale.